2002
DOI: 10.1016/s0014-5793(02)03401-4
|View full text |Cite
|
Sign up to set email alerts
|

Biological effects of group IIA secreted phosholipase A2

Abstract: Group IIA secreted phospholipase A 2 (sPLA 2 -IIA) is the most abundant element in human tissues of a large family of low molecular weight phospholipases A 2 , which shows properties di¡erent from those displayed by the cytosolic phospholipase A 2 involved in the release of arachidonic acid. sPLA 2 -IIA behaves as a ligand for a group of receptors inside the C-type multilectin mannose receptor family and also interacts with heparan sulfate proteoglycans such as glypican, the dermatan/chondroitin sulfate-rich d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
27
0
1

Year Published

2004
2004
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 72 publications
(51 reference statements)
1
27
0
1
Order By: Relevance
“…In addition to cPLA 2 and iPLA 2 , sPLA 2 also plays a role in inducing apoptotic process (Sun et al, 2004(Sun et al, , 2007Lee et al, 2006). In terms of the findings that sPLA 2 induced the production of TNF-a in murine macrophage RAW 264.7 cells and expression of FasL in monocytic cells (Fuentes et al, 2002;Lee et al, 2006), it is interesting to explore whether sPLA 2 could upregulate TNF family receptor in leukemia cells. Our recent finding showed that Naja naja atra PLA 2 induced apoptotic death of human leukemia U937 cells (Chiou et al, 2008).…”
mentioning
confidence: 99%
“…In addition to cPLA 2 and iPLA 2 , sPLA 2 also plays a role in inducing apoptotic process (Sun et al, 2004(Sun et al, , 2007Lee et al, 2006). In terms of the findings that sPLA 2 induced the production of TNF-a in murine macrophage RAW 264.7 cells and expression of FasL in monocytic cells (Fuentes et al, 2002;Lee et al, 2006), it is interesting to explore whether sPLA 2 could upregulate TNF family receptor in leukemia cells. Our recent finding showed that Naja naja atra PLA 2 induced apoptotic death of human leukemia U937 cells (Chiou et al, 2008).…”
mentioning
confidence: 99%
“…Recent studies have focused on three major groups of PLA 2 : the group IV calcium-dependent cytosolic PLA 2 (cPLA 2 ), the group II secretory PLA 2 (sPLA 2 ), and the group VI Ca 2 ϩ -independent PLA 2 (iPLA 2 ) (9). Dur-ing the past decade, excellent reviews describing the structure and properties of these PLA 2 s in non-neural systems have appeared (7)(8)(9)(10)(11). In addition, two reviews focusing on PLA 2 in brain tissue have also been published (12,13).…”
mentioning
confidence: 99%
“…Among these, the group IIA sPLA 2 (sPLA 2 -IIA) has been studied extensively because of its involvement in inflammatory processes (Fuentes et al 2002). Up-regulation of sPLA 2 -IIA mRNA expression has been reported in rat brain after transient global ischemia (Lauritzen et al 1994) and an increase in sPLA 2 activity was observed after photochemically induced focal cerebral ischemia (Yagami et al 2002).…”
mentioning
confidence: 99%